PERSEPSI PETANI TERHADAP ZAKAT HASIL SAWIT DAN KARET DI KECAMATAN ANGKOLA SANGKUNUR KABUPATEN TAPANULI SELATAN - Batubara, Damri (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Zakat is an obligation that Muslims must fulfill if their qualities and conditions are met. Zakat also has an active role in the economic system. Because zakat is a levy that encourages economic life to create certain influences. When looking at the available data calculated the income of oil palm and rubber farmers in a year (haul period), has reached the obligatory nishab size of zakat. However, the oil palm and rubber farmers do not issue zakat as the rule should be. Therefore, it is necessary to know how the perception of the farmers to the zakat of oil palm and rubber and what are the factors that cause oil palm and rubber growers or do not issue zakat.